The application of innovative joint control strategies in the synergistic optimization of enterprise procurement, production, rework and quality control - Qingyu Hong; Jiping Qi; Hao Yin; Jie Gu; Hong Shen; Jihua Fan (PLoS ONE, 2026)
This study proposes an innovative joint control strategy for enterprise collaborative optimization in procurement, production, rework, and quality control in mechanical component manufacturing enterprises. A comprehensive model unifies supplier selection, rework decisions, and quality sampling is developed, thereby addressing the fragmentation of single-stage optimization in existing studies. In procurement, a confidence-interval-based model screens suppliers, with sample size determined by binomial distribution, factoring in two types of error risks to optimize costs. A cost-benefit model for production evaluates rework feasibility. For quality control, a fraction-f sampling plan balances inspection costs and product quality. The model is solved and simulated using MATLAB, and sensitivity analysis is conducted. The analysis reveals that the spare-part defect rate significantly impacts total profit, stressing procurement quality control. The defect rate of semi-finished products has minimal impact, indicating effective controls. An increase in the finished-product defect rate raises costs and reduces profits. These results demonstrate the effectiveness of the proposed joint control strategy in optimizing the cost-quality balance.